India, Myron Weiner and the political science of development - Brass, Paul R. (2002)
The argument here, in brief, is that the political science of development has itself been implicated in the developmentalist framework of India's elites. Further, despite the rhetoric of socialism that acompanied that framework under Nehru, both the practice in India and the development theory that justified it were fundamentally conservative. The conservative elements in the developmentalist framework comprised an ideology of state-exaltation arising out of a 'fear of disorder' or an orientation towards the elimination of 'the causes of unrest'. So implicated were political scientists in the developmentalist goals of India's elites that they failed to provide an independent basis for critique that has become increasingly necessary as it has become more and more obvious that those goals have failed to transform India into the modern, industrial state of its elite's imaginings, have failed at the same time to provide for the basic minimum needs of its people, have failed to eliminate 'the causes of unrest' and have instead drawn the country into the ugly morass of state terrorism in the north-east, Punjab and Kashmir and have failed to provide a basis for accommodation between the Hindu and Muslim populations of the country. - Reproduced.
Keywords: Political science; Weiner, Myron